PENGARUH KARAKTERISTIK DEWAN PENGAWAS SYARIAH TERHADAP KINERJA PERBANKAN YANG DIMODERASI OLEH PENGAMBILAN RISIKO BANK (Studi Pada Bank Syariah Di Asia Tenggara Periode 2015-2019) - Rizki, Marsi Fella; Husaini, Husaini; Ilyas, Fitrawati (UNIB Press, 2021)
This study aims to find empirical evidence regarding the effect of the characteristics of the Sharia Supervisory Board on the performance of Islamic banking and whether there is a moderating effect of risk taking. The characteristics of the Sharia Supervisory Board in this study consist of the size of the Sharia Supervisory Board, the education of the Sharia Supervisory Board in the field of finance and Islamic banking, the Sharia Supervisory Board’s foreign scholar, and the Sharia Supervisory Board's busy. The population in this study were all Islamic banks in Southeast Asia in 2015-2019. Based on sampling through purposive sampling technique, 27 samples of Islamic banks. This research data analysis method is WrapPLS. By using WrapPls, the research finds that the Sharia Supervisory Board has a positive and significant effect on bang performance, and risk taking moderates the effect of the Sharia Supervisory Board on bank performance.